Double-layer ITO/Al back surface reflector for single-junction silicon photoconverters - Kopach, V.R.; Kirichenko, M.V.; Shramko, S.V.; Zaitsev, R.V. (Functional Materials, 2008)
It has been shown that to increase the efficiency and manufacturability of single-crystal silicon photovoltaic solar energy converters (Si-PVC) with 180-200 μm thick base crystals having a polished photoreceiving surface and double-layer back surface reflector (BSR) consisting of a transparent oxide and aluminum layers, a conductive transparent indium-tin oxide (ITO) layer of 0.25 μm interference thickness is to be used as the nonmetallic BSR layer. It provides the ITO/Al BSR reflection coefficient in the range of 85 < R < 96 % for solar radiation photoactive component incident the Si-PVC back surface at substantially zero contribution of ITO layer resistance to the device series resistance. In the case of Si-PVC with inverted pyramid type texture of crystal photoreceiving surface at which the specificity of light distribution in the crystal causes total reflection of radiation from Si/ITO interface, the ITO layer thickness should be experimentally optimized in the 1-2 μm range independently of base crystal thickness to minimize the photoactive radiation losses and ITO layer resistance.